-

= ò ò Q(x,y)dxdy

xi-   ½ yj- ½

:

Ex(x,y) = - dj(x,y)

dx (*)

Ey(x,y) = - dj(x,y)

dy

x - .

 


yj-½ < y < yj- ½ Ex(xi + ½,yj) = Ei+ ½ ,j = const

yj-½ < y < yj- ½ Ex(xi - ½ ,yj) = Ei- ½ ,j = const (**)

xi-½ < x < xi+ ½ Ey(xi, yj + ½) = Ei,j+ ½ = const

xi-½ < x < xi+ ½ Ey(xi, yj ) = Ei,j - ½ = const

xi- ½ < x < xi+ ½

yj- ½ < y < yj+ ½ - Q(x,y) = Qij = const


 


(Ex)i+ ½ ,j - (Ex)i -½ ,j r*j + (Ey)ij+ ½ - (Ey)ij- ½ h*i = Qijh*i r*j

h*i = hi - hi+1 , r*j = rj - rj+1

2 2

i+ ½ ,j j(x,y) :

xi+1

òEx(x,yj)dx = - ji+1,j - jij

xi

(**) y=yj:


(Ex)i+ ½ ,j = - ji+1j - jij

hi+1

:

(Ey)i,j+ ½= - jij+1 - jij

rj+1


:

 


(Dj)ij = 1 j i+1,j - j ij - j i j - j i-1,j + 1 j i j+1 - j ij - j ij - j ij-1 =

h*i hi+1 hi r*j rj+1 rj


= Ndij + Naij





















 


SiO2

e1









Si y

en








x





V0j

yj+ ½ x ½

ene0 ò(Ex(x ½ ,y) - E+x(0,y))dy + ene0 ò (Ey(x,yj+ ½) - Ey(x,j- ½ ))dx =

yj- ½ 0

x ½ yj+½

= q ò ò (Nd + Na)dxdy

0 yj-½

V`0j

yj+ ½ x ½

ene0 ò(E-x(0,y) - Ex(x -½,y))dy + ene0 ò (Ey(x,yj+½) - Ey(x,j-½))dx = 0

yj- ½ 0

 

E+x(0,y) E-x(0,y) -

.

:


ene0 dj + - e1e0 dj - = -Qss

dx dx


yj+½ x½

ò (ene0Ex(x½,y) - e1e0Ex(x-½,y) - Qss(y))dy + ene0ò (Ey(x,yj+½) + Ey(x,yj-½))dx +

yj-½ 0

0 x½ yj+½

+ e1e0 ò (Ey(x,yj+½) - Ey(x,yj-½))dx = q ò ò (Nd + Na)dxdy

x-½ 0 yj-½


Ex Ey (**) Qss(y) = Qss = const yj-½ < y < yj+½ :

 

j+ = j- dj + = dj -

dy dy

+-

- -

:


 


ene0(Ex)½,j - e1e0(Ex)-½,j - Qss r*j + ene0h1 + e1e0h-1 . (Ey)0,j+½ - (Ey)0,j-½ =

2 2


= q (Nd0j - Na0j) h1r*j

2

:

 


1 ene0 jij -j0j - e1e0 j0j - jij + ene0h1 + e1e0h-1 j0,j+1 - j0j - j0j - j0,j-1 =

h* h1 h-1 2h*r*j rj+1 rj

: 1, 2, 3, 4